Anthracnose disease of walnut (Juglans regia) in Kashmir valley - Z.A. BADRI*, N.A. KHAN; Z.A. BHAT, MUDASIR HASSAN, KHURSHID AHMAD (Indian Phytopathology, 2017)
Walnut anthracnose is one of the most important disease of walnut (Juglans regia L.) worldwide. In earlier stages of the disease development, spots are circular light brown slightly sunken which later on turned dark brown in colour with irregular margins. Maximum disease development in the field was observed during August and spots attained maximum size of 27-29 mm. The disease symptoms on the twigs initially appeared as dark brown oval lesions which later on turned black in colour with irregular margins attained maximum size of 26-27 mm. The pathogen produced white glaborus raised colony, which later turn creamy white to grayish white with well-defined lobate margins and concentric zones. Acervulus (113.48-190.49Âµm) appears in concentric rings having hyaline guttulated, crescent conidia (23.58 Ã— 10.13Âµm). Maximum mycelia growth was achieved on corn meal agar, whereas potato dextrose agar proved to be best media for sporulation of isolatedÂ pathogen (M. juglandis). The fungus requires incubation period of 14-18 days to produce symptoms on potted walnut seedlings.